Phase II study of tosedostat with cytarabine or decitabine in newly diagnosed older patients with acute myeloid leukaemia or high‐risk MDS. (16th November 2015) - Mawad, Raya; Becker, Pamela S.; Hendrie, Paul; Scott, Bart; Wood, Brent L.; Dean, Carol; Sandhu, Vicky; Deeg, Hans Joachim; Walter, Roland; Wang, Lixia; Myint, Han; Singer, Jack W.; et al.
Abstract: Tosedostat, an oral aminopeptidase inhibitor, has synergy with cytarabine and hypomethylating agents. We performed a Phase II trial to determine rates of complete remission (CR) and survival using tosedostat with cytarabine or decitabine in older patients with untreated acute myeloid leukaemia (AML) or high‐risk myelodysplastic syndrome (MDS). Thirty‐four patients ≥60 years old (median age 70 years; range, 60–83) were randomized to receive tosedostat (120 mg on days 1–21 or 180 mg continuously) with 5 d of either cytarabine (1 g/m 2 /d) or decitabine (20 mg/m 2 /d) every 35 d. Twenty‐nine patients (85%) had AML, including 15 (44%) with secondary AML/MDS, and 5 (15%) had MDS‐refractory anaemia with excess blasts type 2. The CR/CR with incomplete count recovery (CRi) rate was 53% [9 in each arm; 14 CR (41%) and 4 CRi (12%)], attained in 6 of 14 patients with adverse cytogenetics and 4 of 7 with FLT3 ‐internal tandem duplication mutations. Median follow‐up was 11·2 months (range, 0·5–22·3), and median survival was 11·5 months (95% confidence interval, 5·2–16·7). Twenty‐three patients (67·6%) were treated as outpatients and 10 of these patients required hospitalization for febrile neutropenia. No Grade 3–4 non‐haematological toxicities required withdrawal from study. Tosedostat with cytarabine or decitabine is tolerated in older patients with untreated AML/MDS, results in a CR/CRi rate of >50%, and warrants further study in larger trials.